Effects of Sports Drinks on Weight Loss Control and Lipid Metabolism in Overweight Students - Qiufen Yu; Liubai Shan; Lei Du; Jiali Zang (Journal of Food Quality)
In order to explore how sports drinks can achieve weight loss control and lipid metabolism in college students, the author proposes an experiment based on weight loss control and lipid metabolism in college students. This experiment recommends key technical problems and solutions based on information represented by college students’ weight loss control, a study exploring how sports drinks can achieve weight loss control in college students. Research has shown that Jupu sports drink is more suitable than 87% of sports drinks on the market for college students to lose weight. Sports drinks have a positive effect on maintaining a high blood sugar level during exercise and have a certain antifatigue effect in mass fitness. Jupu sports drink not only has the effect of other sports drinks but also has a certain effect on weight loss control.